Engineering of Lipid Nanoparticles by the Multifunctionalization of the Surface with Amino Acid Derivatives for the Neutralization of a Target Toxic Peptide. (5th October 2020) - Koide, Hiroyuki; Hirano, Satoshi; Ide, Takafumi; Saito, Kazuhiro; Suzuki, Hikaru; Yasuno, Go; Hamashima, Yoshitaka; Yonezawa, Sei; Oku, Naoto; Asai, Tomohiro
Abstract: Protein affinity reagents (e.g., antibodies) are often used for basic research, diagnostics, separations, and disease therapy. Although a lot of "synthetic" protein affinity reagents have been developed as a cost‐effective alternative to antibodies, their low biocompatibility is a considerable problem for clinical application. Lipid nanoparticles (LNP) represent a highly biocompatible drug delivery agent. However, little has been reported that LNP itself works as a protein affinity reagent in living animals. Here, LNP is engineered for binding to and neutralizing a target toxic peptide in living animals by multifunctionalization with amino acid derivatives. Multifunctionalized LNP (MF‐LNP) is prepared using amino acid derivative‐conjugated lipids. Optimized MF‐LNP exhibits nanomolar affinity to the target toxic peptide and inhibits toxic peptide‐dependent hemolysis and cytotoxicity. In addition, MF‐LNP captures and neutralizes the toxic peptide after intravenous injection in the bloodstream; in addition, MF‐LNP does not release the toxic peptide in the accumulated organ. These results reveal the potential of using LNP as a highly biocompatible protein affinity reagent such as an antidote. Abstract : It is shown that lipid nanoparticles multifunctionalized with amino acid derivatives can act as a protein affinity reagent by mimicking protein–protein interactions and captures and neutralizes target molecules in the bloodstream of living mice.